2018
DOI: 10.22498/pages.26.2.54
|View full text |Cite
|
Sign up to set email alerts
|

Open-data practices and challenges among early-career paleo-researchers

Abstract: belmont Forum (2018) retrieved August 6, from bfe-inf.org/action-theme-4-capacity-buildinghuman-dimensions Data Tree (2016) retrieved August 6 from datatree.org.uk Kaufman D, PAGES 2k Special Issue Editorial Team (2018) Clim Past 14: 593-600 PAGES Early-Career Network (2018) retrieved July 6, from groups.google.com/forum/#!topic/ pages-early-career-network/rOp6Hc7J6fc Wilkinson MD et al. (2016) Sci Data 3: 160018 Figure 2: Selected survey responses (%; n=183) grouped by research experience. Non-tenure encompas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Unique dataset identifiers could, in turn, be adopted to track data reuse and credit the authors ( Pierce et al 2019 ). Normalizing these practices begins with data stewardship training to highlight resources (e.g., https://fairsharing.org ) and community standards (e.g., Biodiversity Information Standards, https://www.tdwg.org ) when managing paleobiological data ( Koch et al 2018 ; Seltmann et al 2018 ; Stall et al 2018 ; Krimmel et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unique dataset identifiers could, in turn, be adopted to track data reuse and credit the authors ( Pierce et al 2019 ). Normalizing these practices begins with data stewardship training to highlight resources (e.g., https://fairsharing.org ) and community standards (e.g., Biodiversity Information Standards, https://www.tdwg.org ) when managing paleobiological data ( Koch et al 2018 ; Seltmann et al 2018 ; Stall et al 2018 ; Krimmel et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This evolving character along with the long-term sustainability problems contributes to the lack of evaluation of these programs in their impact on ECs and data cultures. Exploratory qualitative studies have shown, though, that the challenges of acculturating ECs into open and transdisciplinary data cultures are associated with the rigid academic reward system, ECs' unfamiliarity with the changing community norms, and lack of training and support (Koch et al, 2018;Nicholas et al, 2019). How can interdisciplinary acculturation help to develop skills to thrive in data-intensive environments, while learning to appreciate epistemic diversity and different types of data?…”
Section: Introductionmentioning
confidence: 99%